Oral supplement in healthy older adults to support physical fitness and mental wellbeing - Lloyd, Amanda J.; Nash, Robert J.; Warren-Walker, Alina; Watson, Alison; Martinez Martin, MJ Pilar; Davies, Courtney; Villarreal-Ramos, Bernardo; Wilson, Thomas; Beckmann, Manfred (Frontiers in Nutrition, 2025)
IntroductionCucumbers have been anecdotally credited with anti-inflammatory properties. IdoBR1 [(2R,3R,4R,5S)-3,4,5-trihydroxypiperidine-2-carboxylic acid], an iminosugar amino acid isolated from the fruits of certain cucumbers (Cucumis sativus, Cucurbitaceae), has been demonstrated to possess anti-inflammatory activity. Q-actin™ is a quality-controlled cucumber extract containing measured idoBR1, which has shown promising results in the treatment of osteoarthritis through oral administration.MethodsA healthy middle-aged and older adult population was recruited and randomized to receive either Q-actin™ (2 × gummies containing 10 mg Q-actin™ daily) or matched placebo gummies for 12 weeks. Physical strength and finger dexterity were assessed using hand grip strength and the Nine-Hole Peg Test, respectively. We evaluated diet choices with the Prime Diet Quality Score and sleep quality with the Pittsburgh Sleep Quality Index and collected first-morning urine samples for chemical composition analysis using Flow Infusion Electrospray Ionization Mass Spectrometry (FIE-MS).ResultsWe recruited a cohort of 47 healthy middle-aged and older adults (ages 50–78; 15 men and 32 women). FIE-MS analysis on urines was conducted and we tentatively identified elevated melatonin derivatives after Q-actin™ supplementation, suggesting a positive effect on sleep quality, which correlated with self-reported Pittsburgh Sleep Quality Index. The relative m/z-transition areas of melatonin and its two main biotransformation products in selected urine samples after Q-actin™ supplementation were confirmed following LC-MS/MS fragmentation.ConclusionQ-actin™ demonstrated potential benefits in a healthy middle-aged and older adult population by improving sleep quality, as evidenced by elevated melatonin derivatives identified in urine samples and self-reported improvements on the Pittsburgh Sleep Quality Index and improved finger dexterity. These findings support the hypothesis that Q-actin™ may have positive effects on overall wellbeing, as shown here in healthy older people, and could be rated to enhanced sleep quality.Clinical trial registrationISRCTN registry ISRCTN28705061 and clinicaltrials.gov/ NCT05878847.